2016
DOI: 10.3109/02688697.2015.1119241
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytomegalovirus in glioblastoma multiforme: Myth or reality?

Abstract: A role for human cytomegalovirus (HCMV) in the pathogenesis of glioblastoma multiforme (GBM) was proposed more than a decade ago and has since generated a considerable debate as a possible therapeutic target. We investigate the presence of HCMV in the specimens of patients with GBM treated in our centre. This is a retrospective cohort study to investigate the presence of HCMV by routine immunohistochemical stains and polymerase chain reaction (PCR)-based molecular analysis on formalin-fixed-paraffin-embedded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…In addition to the probes, denaturation, hybridization and detection could be different, and might account for the different outcomes. Similar to our results, a recent report showed no expression of HCMV in 32 GBM by IHC and RT-PCR HCMV assay [39]. …”
Section: Discussionsupporting
confidence: 93%
“…In addition to the probes, denaturation, hybridization and detection could be different, and might account for the different outcomes. Similar to our results, a recent report showed no expression of HCMV in 32 GBM by IHC and RT-PCR HCMV assay [39]. …”
Section: Discussionsupporting
confidence: 93%
“…originating form cervical or head and neck tissues), indicating that CDV may be considered a broad-spectrum anti-tumor agent. Hadaczek et al also showed that CDV inhibits glioblastoma both in vitro and in vivo , regardless of the presence of human cytomegalovirus (HCMV) [25], however a role for HCMV in the pathogenesis of glioblastoma is controversial [35]. It was previously shown that the in vitro and in vivo antiproliferative activities of CDV against nasopharyngeal carcinoma (which is driven by Epstein-Barr virus) were not due to inhibition of the viral DNA polymerase [27].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies show a positive association between HCMV and gliomas [ 1 , 20 39 ]. Nevertheless, there are investigations that could not confirm the presence of the virus in the tumors and controversy in the field persists [ 19 , 40 47 ]. In addition, few studies investigated the correlation between expression of viral genes and proteins in gliomas with tumor malignancy [ 20 , 30 , 36 , 37 , 48 ].…”
Section: Introductionmentioning
confidence: 99%